Factors associated with the length of stay in total knee arthroplasty patients with the enhanced recovery after surgery model - Guoqing Li (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Objectives The purpose of this study is to identify the factors that influence the length of stay (LOS) in total knee arthroplasty (TKA) patients with an enhanced recovery after surgery (ERAS) program. Methods Information from 167 patients (31 males and 136 females, range from 43 years to 88 years old) who underwent the unilateral elective primary TKA from January 2017 to January 2019 were reviewed retrospectively. Factors were analyzed by single-factor variance and multi-factor linear regression. Results By single-factor variance analysis, American Society of Anesthesiologists (ASA) physical status classification system, pre-operation albumin, pre-operation erythrocyte sedimentation rate (ESR), primary and merge diseases, hidden blood loss, and length of operation were correlated with LOS (P < 0.05). Multi-factor linear regression results suggested that gender, ASA class, pre-operation Alb, and pre-operation ESR were associated with LOS (P < 0.05). Moreover, ASA class 3 (B value 4.84), pre-operation Alb < 30 g/L (B value 18.33), and pre-operation ESR > 15 mmol/h (B value 2.21) could increase the LOS, while males (B value − 3.56) had a shortened LOS. Conclusions Overall, our research found that female, ASA class 3, pre-operation Alb < 30 g/L, and pre-operation ESR > 15 mmol/h could extend LOS in TKA patients with ERAS.